2007
DOI: 10.1093/bja/aem244
|View full text |Cite
|
Sign up to set email alerts
|

Detection of oesophageal intubations using cuff pressures in a pig trachea–oesophagus model

Abstract: We conclude that the cuff pressures may be useful in detecting oesophageal intubations. This method is faster than other confirmation measures as it can detect inadvertent oesophageal intubations at the time of inflating the cuffs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…However, the animals were placed in a dorsal recumbent position and were not paralyzed. The same laboratory repeated the study using tracheal-esophageal tissue preparations harvested from adult pigs with similar conclusions [16]. Using a human cadaveric model, Russo et al, found conflicting results with esophageal and tracheal pressures demonstrating no significant difference with cuff volumes exceeding 3 mL [17].…”
Section: Cuff Volume (Ml)mentioning
confidence: 82%
See 2 more Smart Citations
“…However, the animals were placed in a dorsal recumbent position and were not paralyzed. The same laboratory repeated the study using tracheal-esophageal tissue preparations harvested from adult pigs with similar conclusions [16]. Using a human cadaveric model, Russo et al, found conflicting results with esophageal and tracheal pressures demonstrating no significant difference with cuff volumes exceeding 3 mL [17].…”
Section: Cuff Volume (Ml)mentioning
confidence: 82%
“…Exclusion criteria included subject refusal, emergency surgery, increased risk of aspiration, known or expected difficult intubation, contraindication to the use of succinylcholine, and a history of esophageal or tracheal pathology. The study protocol was formulated by combining key aspects of the previous studies performed on porcine models [15,16] and human cadaveric subjects [17], as well as integrating standard patient intubation techniques and monitoring to ensure amnesia, analgesia, and muscular relaxation during our study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural differences in the trachea and esophagus provide a differential compliance during cuff inflation as demonstrated in porcine models. 1,2 This could be the basis of a new method of rapidly and accurately confirming tube placement. We seek to extend this investigation to human cadaveric models by measuring and comparing esophageal and tracheal compliance curves.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical assessments of tube position including chest auscultation are unreliable . Thus, various methods for verifying endotracheal tube position have been developed . However, all the current methods can fail and be impractical, particularly in emergency settings such as cardiac arrest .…”
mentioning
confidence: 99%